1990
DOI: 10.1111/j.1469-7998.1990.tb04041.x
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of cranial sexual dimorphism in certain groups of extant hominoids

Abstract: This paper presents a study of patterns of cranial variation within and between extant hominoids. Particular attention is paid to the relationship between sexual dimorphisms and size differences between sexes. It emerges that shape contrasts between sexes are closely linked to size differences whilst variance dimorphism appears to be relatively independent of size effects. This study demonstrates that there are differences between the hominoids in their magnitudes and patterns of sexual shape contrasts. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
0
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 22 publications
5
27
0
2
Order By: Relevance
“…Our results support numerous studies that have confirmed sexual dimorphism of cranial dimensions in gorillas (O'Higgins et al, 1990;Wood et al, 1991;O'Higgins and Dryden, 1993;Uchida, 1996;Lockwood, 1999;Schaefer et al, 2004). These studies have also shown that there is a high variability of dimorphism among the dimensions studied.…”
Section: Sexual Dimorphism In Head Sizesupporting
confidence: 94%
“…Our results support numerous studies that have confirmed sexual dimorphism of cranial dimensions in gorillas (O'Higgins et al, 1990;Wood et al, 1991;O'Higgins and Dryden, 1993;Uchida, 1996;Lockwood, 1999;Schaefer et al, 2004). These studies have also shown that there is a high variability of dimorphism among the dimensions studied.…”
Section: Sexual Dimorphism In Head Sizesupporting
confidence: 94%
“…Overall, the results of this study introduce many interesting avenues for future investigation, while highlighting the caution with which studies of ontogeny have to be approached. As an example, one of the authors has shown that adult sexual dimorphisms can differ to greater or lesser degree, not only between different primate species but also between modern human populations (O’Higgins et al. 1989, 1990a, 1990b; O’Higgins, 1989).…”
Section: General Conclusionmentioning
confidence: 99%
“…Skeletal dimorphism is not uniformly expressed as a simple function of body mass dimorphism in primates (Oxnard, 1987;O'Higgins et al, 1990;Plavcan, in press), and in fact appears to be very complex in the pattern of its expression both within and among species. In most species, measurements of the brain case, basicranium, and orbits tend to show less dimorphism than measurements of the face and jaws ( Fig.…”
Section: "Reverse Dimorphism"mentioning
confidence: 99%